Pembelajaran Vokal Di SMP Negeri 1 Payakumbuh - Danil Guntara; Irdhan Epria Darma Putra (SENDRATASIK UNP, 2021)
This study aims to describe Vocal Learning in SMP 1 Payakumbuh. This research used qualitative approach, and it belongs to descriptive research. The data were collected through observation, interview, and documentation. The data analysis was conducted through data collection, data reduction, data presentation, and conclusion drawing .Data validity test was done by extending observations and increasing persistence. The results of this study indicate that: (1) lesson planning includes: a. The material being taught is provided in stages, b. The methods used are the lecture method, demonstration method, question and answer method, and assignment method, (2) the implementation of vocal learning includes: initial activities, core activities, and final activities, (3) learning evaluation includes process evaluation seen from students’ discipline, activeness, and seriousness. In addition, evaluation of results seen from the activities when students demonstrate. It uses indicators of techniques, material, and appearance.